A very private person - Grossick, Hannah (The Pentland Press, 1998)
This novel was inspired by the plight of transsexual people. Aimed at the general public, its purpose is to instruct rather than to titillate. It is the Author's hope that it will be of some value to the families of those who may be undergoing gender reassignment, enabling them to anticipate some of the issues to be confronted and to understand the perspective of the transsexual person. this work succeeds in both bringing about a greater understanding of the issues involved, as well as being a highly entertaining, well-written work.